Diagnostic performance of susceptibility-weighted magnetic resonance imaging for the detection of calcifications: A systematic review and meta-analysis. Issue 1 (December 2017) - Adams, Lisa; Bressem, Keno; Böker, Sarah; Bender, Yi-Na; Nörenberg, Dominik; Hamm, Bernd; Makowski, Marcus
Abstract Since its introduction, susceptibility-weighted-magnetic resonance imaging (SW-MRI) has shown the potential to overcome the insensitivity of MRI to calcification. Previous studies reporting the diagnostic performance of SW-MRI and magnetic resonance imaging (MRI) for the detection of calcifications are inconsistent and based on single-institution designs. To our knowledge, this is the first meta-analysis on SW-MRI, determining the potential of SW-MRI to detect calcifications. Two independent investigators searched MEDLINE, EMBASE and Web of Science for eligible diagnostic accuracy studies, which were published until March 24, 2017 and investigated the accuracy of SW-MRI to detect calcifications, using computed tomography (CT) as a reference. The QUADAS-2 tool was used to assess study quality and methods for analysis were based on PRISMA. A bivariate diagnostic random-effects model was applied to obtain pooled sensitivities and specificities. Out of the 4629 studies retrieved by systematic literature search, 12 clinical studies with 962 patients and a total of 1, 032 calcifications were included. Pooled sensitivity was 86.5% (95%-confidence interval (CI): 73.6–93.7%) for SW-MRI and 36.7% (95%–CI:29.2–44.8%) for standard MRI. Pooled specificities of SW-MRI (90.8%; 95%–CI:81.0–95.8%) and standard MRI (94.2; 95%–CI:88.9–96.7%) were comparable. Results of the present meta-analysis suggest, that SW-MRI is a reliable method for detecting calcifications in soft tissues.